Experimental and numerical investigation on in-plane compression and shear performance of a pultruded GFRP composite bridge deck. (15th November 2017) - Xin, Haohui; Mosallam, Ayman; Liu, Yuqing; Xiao, Yi; He, Jun; Wang, Congzhe; Jiang, Zhibo
Abstract: The in-plane compression and shear performance plays a significant role in achieving an optimum and reliable design of pultruded glass fiber-reinforced polymer (GFRP) bridge deck supported on steel girders that have been used in bridge decks retrofit application or new construction in the past decade. This paper presents a summary of several laboratory experiments that were performed on a pultruded GFRP bridge deck for pedestrian or light vehicular loading in order to evaluate both the deck's in-plane compression and shear properties. The experimental results showed that the average web thickness has a relatively larger influence on the in-plane shear behavior than the in-plane compressive behavior. Three-dimensional finite element models utilizing the Hashin's theory laminate failure, adhesive layers failure via cohesive element and initial geometry imperfections by using limited critical eigenmodes multiplied by empirical coefficient were employed to numerically simulate both the deck's in-plane compression and shear ultimate capacity and stiffness based on elastic engineering constants obtained from micromechanics. The numerical results agreed well with experimental results that could provide a reference for the design and construction of such type of pultruded composite bridge decks.